2000
DOI: 10.1105/tpc.12.7.1179
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Dilysine Motif Confers Endoplasmic Reticulum Localization to Type I Membrane Proteins in Plants

Abstract: The tomato Cf-9 disease resistance gene encodes a type I membrane protein carrying a cytosolic dilysine motif. In mammals and yeast, this motif promotes the retrieval of type I membrane proteins from the Golgi apparatus to the endoplasmic reticulum (ER). To test whether the C-terminal KKXX signal of Cf-9 is functional as a retrieval motif and to investigate its role in plants, green fluorescent protein (GFP) was fused to the transmembrane domain of Cf-9 and expressed in yeast, Arabidopsis, and tobacco cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 97 publications
(92 reference statements)
2
88
1
Order By: Relevance
“…The pattern was unlike those described for the plasma membrane (Panek et al, 2000), the tonoplast (Suriapranta et al, 2000), or the Golgi (Ton et al, 2002) but was similar to that shown for the endoplasmic reticulum (Benghezal et al, 2000). Although no discrete signal was apparent at the plasma membrane or the vacuolar membrane, the notion that a small proportion of the protein was incorporated into these membranes could not be discounted.…”
Section: Shmtp1 Is Located At the Plant Tonoplastcontrasting
confidence: 39%
See 1 more Smart Citation
“…The pattern was unlike those described for the plasma membrane (Panek et al, 2000), the tonoplast (Suriapranta et al, 2000), or the Golgi (Ton et al, 2002) but was similar to that shown for the endoplasmic reticulum (Benghezal et al, 2000). Although no discrete signal was apparent at the plasma membrane or the vacuolar membrane, the notion that a small proportion of the protein was incorporated into these membranes could not be discounted.…”
Section: Shmtp1 Is Located At the Plant Tonoplastcontrasting
confidence: 39%
“…The resulting cassette was removed as a NotI fragment, inserted into the NotI site of pPLEX502, and transferred to Agrobacterium as described above. A similar construct was prepared for the expression of a ShMTP1:GFP fusion protein in yeast except that the GFP was derived from the plasmid pCBJ4 (Benghezal et al, 2000), because the GFP version optimized for plant expression showed poor expression in yeast. The ShMTP1 cDNA that lacked a stop codon was inserted into the EcoRI site of pBC SK (Stratagene) with its 3Ј end adjacent to the PstI site.…”
Section: Plant and Yeast Transformationsmentioning
confidence: 99%
“…On the other hand, the COOH-terminal L 651 KKR 654 of the CTL1b protein has long been recognized as a classical dilysine (KKXX) motif for endoplasmic reticulum (ER) retrieval of type I transmembrane proteins (27). The KKXX motif is cytosolic and interacts directly with the coat protein I (COPI) coat during retrograde protein transport (7,29,65). It is present in the tails of numerous type I transmembrane proteins including ion channels, transporters, and receptors (32,43,52).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in MG132-treated protoplasts, the HA:AtPRA1.B6 levels continuously increased until the 24-h time point. Furthermore, the HA:AtPRA1.B6 levels were much higher in MG132-treated protoplasts than in DMSO-treated protoplasts at both 12 and 24 h. As a control, the level of ERlocalized GKX, a chimeric fusion protein containing the KKXX motif for ER retrieval from the Golgi complex, was examined as a cargo protein marker (Benghezal et al, 2000;Lee et al, 2009). The GKX level was not affected by MG132 treatment, indicating that 26S proteasome-dependent proteolysis is specific to HA:AtPRA1.B6.…”
Section: Atpra1b6 Levels Are Decreased By 26s Proteasome-dependent Dmentioning
confidence: 99%